The Italian Job: Giambattista Vico at the Origin of Edward Said’s Humanism - Scalercio, Mauro (2016)
The aim of this paper is twofold. First, it will try to clarify the importance of the Italian philosopher Giambattista Vico (1668-1744) in shaping Edward Said’s categories. Second, it will shed light on the theoretical importance of such genealogy. From the philological point of view, it is important to show how profound Said’s knowledge of Vico’s work is. Therefore, this paper will follow references to Vico within the whole of Said’s work, from late the sixties ones to the posthumous Humanism and Democratic Criticism.As far as theory is concerned, understanding Said’s use of Vico’s concepts explains why Said refers to his own work with the controversial term “humanism.” Vico, critiquing modernity from the onset, is the basis on which Said built a new critical humanism. In particular, Said uses the very essential elements of the philosophy of Vico: the importance of body as the source of humanity, the critique of modern abstractions, the idea that man knows what he makes, and the idea of the historicity of every human invention and construction.